Importance of silicon and mechanisms of biosilica formation in plants - Sahebi, Mahbod; Musa, Mohamed Hanafi; Abdullah, Siti Nor Akmar; Yusop, Mohd Rafii; Azizi, Parisa; Tengoua, Fabien Fonguimgo; Jamaludin, Nurul Mayzaitul Azwa; Shabanimofrad, Mahmoodreza (Hindawi Publishing Corporation, 2015)
Silicon (Si) is one of the most prevalent macroelements, performing an essential function in healing plants in response to environmental stresses. The purpose of using Si is to induce resistance to distinct stresses, diseases, and pathogens. Additionally, Si can improve the condition of soils, which contain toxic levels of heavy metals along with other chemical elements. Silicon minimizes toxicity of Fe, Al, and Mn, increases the availability of P, and enhances drought along with salt tolerance in plants through the formation of silicified tissues in plants. However, the concentration of Si depends on the plants genotype and organisms. Hence, the physiological mechanisms and metabolic activities of plants may be affected by Si application. Peptides as well as amino acids can effectively create polysilicic species through interactions with different species of silicate inside solution. The carboxylic acid and the alcohol groups of serine and asparagine tend not to engage in any significant role in polysilicates formation, but the hydroxyl group side chain can be involved in the formation of hydrogen bond with Si(OH)4. The mechanisms and trend of Si absorption are different between plant species. Furthermore, the transportation of Si requires an energy mechanism; thus, low temperatures and metabolic repressors inhibit Si transportation.